TRANSLATION TECHNIQUES USED BY ENGLISH THIRD SEMESTER STUDENTS OF UNIVERSITY OF RIAU KEPULAUAN - Erwin Ashari; Marida Hannum Harahap; Shalehoddin Shalehoddin (English Department, University of Riau Kepulauan, Batam,Indonesia, 2022)
Translation is the transferring meaning of the text from source language in which to equivalent text in target language that communicates similar messages by changing structure without changing meaning. The qualitative descriptive method as the research design of this study which aimed to find out translation techniques used by English third semester students in translating a narrative text entitled â€œTelaga Warnaâ€ from English into Indonesian and to describe the dominant technique used by the students in translating the text. The collecting of the data collected taken from the result translation of narrative text from English into Indonesian by 14 participants of English third semester students. In this study, the data analyzed based on translation techniques of Molina and Albir (2002) theory. Based on data analysis, it was found that the translation techniques of narrative text entitled â€œTelaga Warnaâ€ from English into Indonesian done by English third semester students of University of Riau Kepulauan uses fourteen (14) translation techniques found in 1302 data while translating the text. The translation techniques were namely literal translation, calque, reduction, amplification, discursive creation, linguistic amplification, established equivalent, particularization, transposition, linguistic compression, modulation, borrowing, variation, and generalization. The most dominant technique of translation used by students was literal translation techniques